If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 + -8x + -3 = 0 Reorder the terms: -1 + -3 + -8x = 0 Combine like terms: -1 + -3 = -4 -4 + -8x = 0 Solving -4 + -8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -8x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -8x = 0 + 4 -8x = 0 + 4 Combine like terms: 0 + 4 = 4 -8x = 4 Divide each side by '-8'. x = -0.5 Simplifying x = -0.5
| 2n-(-6)=60 | | 9x+2+5x+10=180 | | x^3+4x^2+10x+15=0 | | 0-8x-3= | | n+2=-6+3n | | 0.9354=-638*X+1.087 | | y=(x^3-3)(4x^2+7) | | 2x+4=7x-28 | | 15y-120=12y | | (25-25)/(5-5)=0 | | 2+5+2=250 | | 2cos(4x)=-1 | | 60-2x=76-3x | | 2/x=4/x+2 | | (25-25)/(5-5) | | 4x-30=3x+13 | | -4(2x+3)=-6x+5 | | 2x^2-11x+21=9 | | 5cos^2+4cos=1 | | 3x^2+12x+7=-2 | | 12-3/5x-1/5x-16 | | 2x-3/9-x/6=31-2x/2 | | 16cosx=7 | | 2x^3-32x^2+128x=0 | | y=14+8 | | y=41+8 | | -5=-2u+1 | | -18=4y-2 | | 3(4x-7)=2x+5 | | 2w+1=-3 | | 2x-23=23 | | 36+9y=3x |